Increased Total Renin Levels but Not Angiotensin-Converting Enzyme Activity in Obese Patients with Polycystic Ovary Syndrome - Alphan, Ziynet (Med Princ Pract, 2013)
OBJECTIVE: To investigate the renin-angiotensin-aldosterone system and angiotensin-converting enzyme (ACE) activity in patients with polycystic ovarian syndrome (PCOS). SUBJECTS AND METHODS: In this case-control study, 41 obese (PCOS) women and 29 healthy controls, matched for age and body mass index, were enrolled. Anthropometric, metabolic, and hormonal patterns, including plasma aldosterone, plasma renin, and ACE activity, were measured in each subject. RESULTS: Plasma renin levels were significantly higher in PCOS patients (19.7 ± 14.5 µg/ml) compared with controls (12.9 ± 9.0 µg/ml, p < 0.05). ACE activity and aldosterone levels did not significantly differ between both groups (p = 0.15 and p = 0.18, respectively). Analysis of PCOS patients showed a significant correlation of fasting insulin levels with levels of renin (r = 0.305, p < 0.01) and free testosterone (r = 0.384, p = 0.001). Similarly, homeostasis model assessment index was positively correlated with total renin concentrations (r = 0.366, p < 0.01) and free testosterone (r = 0.352, p < 0.01). CONCLUSION: Obese PCOS women had higher total renin levels, but not ACE activity and aldosterone levels, related to insulin resistance compared with controls.